Analysis of Social Media Marketing Capability and Content Marketing Capability on B2B Marketing Performance with Technology Adoption as a Mediating Variable - Fikri Ikhlasul Amal; Adi Setiawan (International Journal Labs, 2026)
This study aims to analyze the influence of Social Media Marketing Capability and Content Marketing Capability on B2B Marketing Performance with Technology Adoption as a mediating variable in batik MSMEs in Cirebon City. This study uses a quantitative approach with a cross-sectional design. The number of samples of 50 respondents was determined through a non-probability sampling technique with a purposive sampling approach. Data collection was carried out through a questionnaire with a Likert scale, then analyzed using the path analysis method with the help of AMOS. The results of the study show that Social Media Marketing Capability and Content Marketing Capability have a positive and significant effect on B2B Marketing Performance. In addition, these two variables also have a positive and significant effect on Technology Adoption. Furthermore, Technology Adoption has been proven to have a positive and significant effect on B2B Marketing Performance and acts as a partial mediation variable, especially in the relationship between Content Marketing Capability and marketing performance. The research model also shows a good fit, so that it can explain the relationship between variables optimally.